Osteoidosteom: von der Diagnose zur Behandlung = Osteoidosteoma : from diagnosis to treatment - Sprengel, Simon David; Weber, Marc-André; Lehner, Burkhard; Rehnitz, Christoph (Der Radiologe, 2015)
An osteoid osteoma is a benign bone-forming tumor which usually presents in childhood and adolescence and is characterized by extensive nocturnal pain. Computed tomography (CT) is used to reveal the typical radiolucent nidus surrounded by a sclerotic reaction and in magnetic resonance imaging (MRI) a nidal enhancement and perifocal edema can confirm the diagnosis. Having shown excellent success rates radiofrequency ablation has become the treatment of choice which allows minimally invasive and precise destruction of nidal tumor tissue. By using thermal protection techniques and multiple ablation positions successful therapy of perineural tumors and niduses with diameters of more than 2 cm are possible.